Socioeconomic study of domestic water consumption in the Federal District, Brazil - Sant'Ana, Daniel Richard (2016)
Based on the hypothesis that variables such as the cost of water, family income, household size and building typology affect the way water is consumed, this paper describes the results obtained from fieldwork and discusses domestic water consumption for different residential building types of high, mid-high, mid-low and low income dwellings in the Federal District. An econometric model and correlation analysis, using primary data collected in fieldwork, have been estimated for a water demand function in order to understand what lies behind domestic water consumption in the Federal District. The correlation analysis carried out shows a good relationship between indoor water consumption and built area (0.63), dwelling income (0.49), and number of residents (0.37). Estimated water consumption function has shown a relationship between dwelling income and built area. Through multiple regression, indoor and outdoor water consumption functions were estimated for the Federal District. The coefficient of cost of water presented a positive relationship showing that water demand is inelastic to water price due to the fact that water tariff is low, there is no substitute for water, and water tariff represents a small fraction of household income. This study has shown that domestic water consumption increases proportionally to the increase in household income and that it is a function of income, cost of water, household size and typological characteristics of built area.